Non pigmenting mucosal fixed drug eruption due to tadalafil: A report of two cases - Sudip Das; Suchibrata Das; Joyeeta Chowdhury; Dulal Chandra Bhanja (Wolters Kluwer Medknow Publications, 2014)
Various 'sex-stimulant' medicines with fancy names and attractive packaging are available over the counter. Most contain phosphodiesterase 5 inhibitors in various strengths, often with herbal additions. These drugs are used erratically by the lay public, driven by folklore that such usage leads to increase in the length, girth or firmness of the penis. Such indiscriminate use by an otherwise healthy population leads to undue side effects.